Principales tipos de injertos que se practican en plantas de cítricos, en Ecuador - Gamarra Valenzuela, Paola Mayli (2022)
This document details the types of grafts that are practiced on citrus plants in Ecuador. Grafting is a technique that consists of the intimate union of a plant with roots (pattern) and a part of another plant (bud or graft) in such a way that an artificial symbiosis is created and an interaction is established. Grafting offers different advantages to farmers, among them: creating new varieties from selected buds or grafts, improving the conservation of the desired characteristics of the mother plant, reducing the time for flowering, fruit production, uniformity, high productivity and quality. There are various grafting techniques that have been implemented depending on the production objectives and that have been adapted to the morphological physiology of these species. Among the types of grafts we can find the following: Approach grafting, bud grafting and spike grafting. The most suitable grafting technique when carrying out these practices in citrus plantations is T-bud grafting or also called escutcheon due to its characteristics.